Показатели липидного профиля сыворотки крови молодых и старых крыс с алиментарным ожирением на фоне сочетанного применения экстремального охлаждения и ядросодержащих клеток кордовой крови - Чернявская, Е.А.; Бабийчук, В.Г.; Сиротенко, Л.А. (Украинский журнал медицины, биологии и спорта. 2019. 4(6): 356–361., 2019)
Ритмические экстремальные холодовые воздействия, как разновидность общего экстремального охлаждения организма, представляют собой перспективный метод низкотемпературных воздействий. На сегодняшний день накоплено большое количество данных свидетельствующих о положительном влиянии препаратов полученных из кордовой крови, как на разные органы, системы, так и на организм в целом. Не вызывает сомнения тот факт, что липиды играют важную роль в жизнедеятельности как человека, так и животных, поскольку дислипидемия является фактором риска, который определяет наличие и степень тяжести ряда заболеваний. При алиментарном ожирении происходит нарушение липидного обмена и избыточная аккумуляция жиров. На экспериментальной модели алиментарного ожирения изучен липидный профиль сыворотки крови молодых и старых крыс до и после сочетанного применения ритмического экстремального охлаждения и введения криоконсервированных ядросодержащих клеток кордовой крови человека. Установлено, что развитие алиментарного ожирения приводило к возникновению гиперлипидемии и смещению липидного профиля в сторону атерогенности. Возрастал уровень общего холестерина, холестерина липопротеинов низкой плотности и коэффициент атерогенности. Отмечено, что данные изменения липидограммы в большей степени были выражены у старых животных. Показано, что сочетанное использование двух методов способствовало нормализации липидного профиля сыворотки крови, как молодых, так и старых крыс с моделью алиментарного ожирения, приближая его к показателям контрольных животных без ожирения. Уменьшался атерогенный риск за счет снижения уровня общего холестерина, холестерина липопротеинов низкой плотности и коэффициента атерогенности, а также увеличения содержания холестерина липопротеинов высокой плотности, которые в организме выполняют важную функцию, связанную с поддержанием липидного гомеостаза. /////////////////////////////////////////////////////////////////////////////////////////////////////////////////////////////////////////////// Alimentary obesity is a chronic disease with a multifactorial nature, being largely stipulated by the lack of motor activity and hypercaloric nutrition. The obesity increases the morbidity and mortality risks because of various complications and requires an interdisciplinary approach in designing therapeutic and preventive methods. In current science of great interest is the study of cold effect on human and animal body. Scientific and clinical practice has accumulated much information on the positive effect of cord blood on both different organs, systems, cell cultures, and the whole body as well. In alimentary obesity, the lipid metabolism is disturbed and an excess fat is accumulated. Proceeding from the mentioned above the purpose of research was to study the lipid profile of blood serum in young and old experimental animals with alimentary obesity in a combined use of rhythmic extreme cold exposures and cryopreserved preparation of cord blood nucleated cells. Material and methods. The research was performed in 6- and 24-month white outbred male rats. All the animals were divided into 3 groups: the first group consisted of intact rats; the second group comprised control rats with the simulated alimentary obesity; the third group was made up of rats with alimentary obesity on the background of combined application of rhythmic extreme cold exposures and cryopreserved preparation of cord blood nucleated cells. The animals were sacrificed by decapitation on the following day. One week and in a month after rhythmic extreme cold exposures and the introduction of cryopreserved preparation of cord blood nucleated cells, the blood was taken and the serum was obtained for biochemical studies. Alimentary obesity was simulated by the method of V. Baranova, by keeping the animals on a hypercaloric diet. Rhythmic extreme cold exposures was performed in cryochamber to cool the experimental animals (–120оC). The thawed preparation of cord blood nucleated cells was intraperitoneally administered once at a dose of 3×105 CD34+ cells per kilogram of body weight. Results and discussion. During an experimental study, it was found out that the development of nutritional obesity led to the appearance of hyperlipidemia and a shift in the lipid profile towards atherogenicity. The level of total cholesterol, low density lipoproteins and the coefficient of atherogenicity increased. It was also noted that these changes in lipid profile were more pronounced in older animals. The combined use of two methods contributed to the normalization of the serum lipid profile of both young and old rats with a model of nutritional obesity, bringing it closer to the indices of control animals without obesity. Atherogenic risk was reduced by lowering the level of total cholesterol, low density lipoproteins and the atherogenic coefficient, as well as increasing the content of high density lipoproteins.
Indices of Lipid Profile of Blood Serum in Young and Old Rats with Alimentary Obesity on the Background of Combined Application of Extreme Cooling and Cord Blood Nucleated Cells
Чернявская Е.А., Бабийчук В.Г., Сиротенко Л.А. Показатели липидного профиля сыворотки крови молодых и старых крыс с алиментарным ожирением на фоне сочетанного применения экстремального охлаждения и ядросодержащих клеток кордовой крови. Украинский журнал медицины, биологии и спорта. 2019. 4(6): 356–361.
Keywords: алиментарное ожирение; ядросодержащие клетки кордовой крови; ритмические экстремальные холодовые воздействия; липидный профиль